Papan Serba Tahu As A Development Media for Debate Training in Al-Kausar Senior High School - Mar’atun Latifah; Panji Sukoco; Chairunnisa Pratami (Pancaran Pendidikan, 2021)
The problem in this research is the low debate ability of students in the Indonesian debate training at Al-Kausar Senior High School. The aim of this research is to find out the low debate ability of students in the Indonesian debate training at Al-Kausar Senior High School. This research created the smart board named Papan Serba Tahu as one of the development learning media for debate training while learning from home. The method used in this research is ADDIE model developed by Dick and Carry (1996). The ADDIE model is an abreviation of Analysis, Design, Development, Implementation, and Evaluations. The result of this research indicate learning media that Paserta can improve students critical thinking, speaking skills, understanding about debate concept, compose arguments well, and deliver a structure of debate speech according to the task of speaker. This can be evidenced by the increase in the average value of students debate training, from an average value of 72 before used Paserta to 80 after used Paserta. This value is taken by reffering to LDBI assesment guidelines